Financial ratios and stock volatility: empirical evidence from the banking sector - Benita, Rahma Tri (Universitas Padjadjaran, 2026)
Banking stock price volatility is closely related to company performance and fundamental indicators. This study analyzes the short-term and long-term relationships between financial ratios and stock price volatility in the banking sector. Based on the results of the long-term correlation, the Price to Earnings Ratio (P/E) and Dividend Yield (DY) variables are proven to be dominant factors influencing volatility because they are directly related to stock price movements. In the short-term correlation between state-owned banks, there is an inverse relationship between Price to Book and ROE, and Debt to Equity has a significant negative effect on Return on Assets and Dividend Yield, indicating that the debt structure compress profitability and dividend payment capacity. Meanwhile, in private banks, Price to Earnings and Price to Book have a significant negative effect on Debt to Equity, suggests that firms perceived by the market as more profitable and valuable tend to maintain lower leverage levels. In general, in both state-owned and private banks, financial ratios reflect fundamental conditions that influence capital structure, investor expectations, and stock price volatility in the short and long term.